Impactos da Covid-19 em Programas Stricto Sensu da Área de Negócios: possibilidades para a educação a distância - de Oliveira Durso, Samuel (Pontifícia Universidade Católica de São Paulo - PUC/SP, 2023)
This study aimed to identify the level of satisfaction of students of master's and doctoral programs in the business area with the changes introduced by higher education institutions to enable the continuity of the course in the context of the pandemic caused by Covid-19. To meet the proposed objective, a questionnaire was applied to 101 students enrolled in programs in the business area in the first half of 2020. As main results, it was possible to verify that the study participants showed, on average, a moderate level of satisfaction in regarding the adaptations introduced by educational institutions in the context of Covid-19. Furthermore, it was possible to identify that some personal characteristics (gender, marital status, age, and the number of children) and previous contact with long-term distance education courses were statistically significant to explain the differences in the motivational levels presented by the sample. It was also possible to find that the more satisfied with the changes the student was, the greater was his propensity to indicate a graduate course 100% in distance education modality to a friend. Among the main discontents in relation to the adaptations used by the institutions, was the perception of low development of the skills necessary for future work as a teacher, the perception of low interaction between students during emergency remote teaching and the difficulties to deepen knowledge in this modality of learning. The survey results allow us to reflect on the impacts of Covid-19 and the introduction of distance education in the graduate programs in Brazil.

Este estudo objetivou identificar o nível de satisfação dos discentes de programas de mestrado e doutorado da área de negócios com as mudanças introduzidas pelas instituições de ensino superior para viabilizar a continuidade do curso frente ao contexto de pandemia provocada pela Covid-19. Para atender ao objetivo proposto, aplicou-se um questionário em 101 discentes matriculados em programas da área de negócios no primeiro semestre de 2020. Como principais resultados, foi possível constatar que os participantes do estudo mostraram, em média, um nível de satisfação moderado em relação às adaptações introduzidas pelas instituições de ensino no contexto da Covid-19. Além disso, foi possível identificar que características pessoais (gênero, estado civil, idade e número de filhos) e o contato prévio com cursos de longa duração em EAD foram estatisticamente significativos para explicar as diferenças nos níveis motivacionais apresentados. Foi evidenciado, ainda, que quanto mais satisfeito em relação às mudanças o estudante estava, maior era a sua propensão para indicar um curso stricto sensu 100% em EAD para um amigo. Entre os principais descontentamentos em relação às adaptações utilizadas pelas instituições, está a percepção de baixo desenvolvimento das habilidades necessárias para a atuação futura como docente, a percepção de baixa interação entre os discentes durante o ensino remoto emergencial e as dificuldades para aprofundar no conhecimento na modalidade EAD. Os resultados da pesquisa permitem refletir sobre os impactos da Covid-19 e a introdução da EAD na pós-graduação stricto sensu no Brasil.
Impactos da Covid-19 em Programas Stricto Sensu da Área de Negócios: possibilidades para a educação a distância
Impacts of Covid-19 on graduate programs in the business area: possibilities for distance education
Keywords: Covid-19; Graduate Programs; Covid-19; Distance Education; Stricto Sensu; EducaçãoaDistância; Education; Educação